Financial Sustainability of Mobile Technology Deployment for Rural Community Through e3Value Methodology - Chong, Xing Zi; Muhammad Asyraf, Khairuddin; Cheah, Wai Shiang; Yanti Rosmunie, Bujang (SERSC, 2020)
ICT4D is the study of the solution to bridge the digital gaps between the rural and urban area. Among the important projects is to set up a network or Internet facilities to the community. It has been indicated that ICT project is suffering from a sustainability issue. To what extent, the mobile network projects can sustain? We are dealing with a community that demands better network coverage. On one hand, the communication provider requesting for details study prior deployment. How to evaluate network projects? To date, there is neither a methodology or systematic way to evaluate the ICT4D projects. As e3value can measure the financial aspect of a business project, can e3value is used as a method to evaluate the financial sustainability of rural connectivity projects? This project investigates the adoption of e3value to simulate rural connectivity projects. In this paper, the e3value is used to evaluate rural connectivity projects by taking the mobile network infrastructure project as a case study. Hence, a new mechanism is introduced for accessing ICT4D projects. It can serve as a tool and method to justify the ICT4D projects.